2016
DOI: 10.1007/s10549-016-3892-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of phosphatases in ER-negative breast cancers identifies DUSP4 as a critical regulator of growth and invasion

Abstract: Estrogen receptor (ER)-negative cancers have a poor prognosis, and few targeted therapies are available for their treatment. Our previous analyses have identified potential kinase targets critical for the growth of ER-negative, progesterone receptor (PR)-negative and HER2-negative, or “triple-negative” breast cancer (TNBC). Because phosphatases regulate the function of kinase signaling pathways, in this study, we investigated whether phosphatases are also differentially expressed in ER-negative compared to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…It has recently been demonstrated that in physiologic conditions, the activation of MAPK promotes DUSP4 expression, which in turn suppresses ERK, ensuring breast cell turnover. Nevertheless, loss of DUSP4 and its methylation lead to an aberrant cell proliferation in basal-like breast cancers (9,10). In addition, the activation of NF-kB signaling plays a crucial role in downregulating the expression levels of DUSP4 in endothelial cells (46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been demonstrated that in physiologic conditions, the activation of MAPK promotes DUSP4 expression, which in turn suppresses ERK, ensuring breast cell turnover. Nevertheless, loss of DUSP4 and its methylation lead to an aberrant cell proliferation in basal-like breast cancers (9,10). In addition, the activation of NF-kB signaling plays a crucial role in downregulating the expression levels of DUSP4 in endothelial cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…9). In physiologic conditions, the transcription of DUSP4 is MEK-dependent and its expression in turn suppresses ERK, along with p38, JNK1, NF-kB, and Rb (9)(10)(11)(12), ensuring a proper negative feedback control of cellular proliferative stimuli. DUSP4 is differentially expressed among luminal and basal breast cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of DEP1 is associated with increased growth factor receptor signaling and promotes cell growth (12). Recently, Mazumdar et al identified dual specificity phosphatase 4 (DUSP4) as the most commonly underexpressed protein phosphatase in ER-negative breast cancers, and showed that ectopic expression of DUSP4 inhibits the growth and invasive properties of ER-negative breast cancer cells by dephosphorylating growth promoting signaling proteins (13). Similarly, loss of DUSP4 promotes the progression of intraepithelial neoplasms into invasive carcinoma in the pancreas (14).…”
Section: Phosphatases As Tumor Suppressorsmentioning
confidence: 99%
“…Ligand-dependent activation of EGFR represents the critical first step of the transcriptional programs regulated by the MEK/ERK pathway, provided that the tumors lack genetic alterations in pathway components that would render the pathway constitutively active. While activating mutations in the EGFR/RAS/RAF/MEK/ERK pathway are rare in breast cancer, approximately 50% of TNBCs are characterized by hemi- or homozygous deletion of the DUSP4 gene, which leads to aberrant pathway activation [24, 28, 29]. Thus, TNBCs harboring DUSP4 genomic loss should be less dependent on EGFR activation.…”
Section: Introductionmentioning
confidence: 99%